Pengaruh Commuting Stress terhadap Motivasi Kerja pada Karyawan yang Bekerja di Jakarta - Kevin Christian; Yusuf Hadi Yudha (Fakultas Psikologi Universitas Pancasila, 2014)
Employee's motivation is important in improving the productivity of an enterprise, but often the work motivation itself is affected by many factors. One of them is commuting stress. This study aims to determine whether there is a significant effect of commuting stress to work motivation on those who work in Jakarta but live in Jabodetabek, which uses a personal vehicle like car or motorcycle. Respondents of this study were 384 workers that work in Jakarta, divided into South Jakarta, East Jakarta, West Jakarta, Central Jakarta, and North Jakarta. The sampling technique used was cluster sampling. Data analysis techniques used in this study is simple linear regression. Based on calculations, the result showed a significant negative effect of commuting stress on work motivation, which means there is a significant negative effect of commuting stress on work motivation by 12%. From the analysis of dimensions to see one is the most influential dimension affecting the motivation also showed the dimension of people behavioral on the street has the highest influence. In addition, analysis of the differences using ANOVA test also showed a significant difference in the level of commuting stress based on traveling time.